Moving towards fairer regional minimum income schemes in Spain - Adrian Hernández; Fidel Picos; Sara Riscado (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Minimum income schemes are set to provide citizens with a minimum living standard. In Spain, these schemes consist of a heterogeneous and complex collection of regional benefits designed and implemented by the Autonomous Communities. This generates important regional discrepancies among the poorest individuals, undermining equal access, adequate social assistance and ultimately the fairness of these last resort safety nets. Following the recent initiative by the central government to introduce a national minimum income scheme complementing the regional ones, a better understanding of the performance of the existing regional minimum income schemes, in terms of their coverage and adequacy, is of the essence. We assess the budgetary, distributional and poverty effects of the current Spanish regional minimum income schemes, as well as the impact of increasing both coverage rates and adequacy levels. Using the European microsimulation model EUROMOD together with microdata from the European Union Statistics on Income and Living Conditions, we simulate a sequence of theoretical scenarios with different combinations of coverage and adequacy levels using national and regional poverty lines as references. Our results suggest that increasing adequacy would have a higher impact on poverty rates than increasing coverage, but would be less effective to reduce poverty intensity. Importantly, all scenarios imply significant expenditure increases, the more so for larger decreases in poverty intensity, as would be expected. Noticeably, results greatly differ among regions, and are sensitive to measuring poverty under a national or a regional criterion, reflecting Spanish regional disparities in terms of poverty.
Keywords: H53; H75; I38; 330; minimum income; coverage; adequacy; microsimulation; EUROMOD